COMPARATIVE ANALYSIS OF THE MAIN CHARACTER IN THE NOVEL NEGRI 5 MENARA AND THE NOVEL RANTAU 1 MUARA BY AHMAD FUADI AND ITS IMPLICATIONS ON LITERATURE APPRECIATION IN LEARNING INDONESIAN LANGUAGE AT SMA AN NURMANIYAH CILEDUG TANGERANG (LITERARY PSYCHOLOGICAL APPROACH) - Wahid, Abdul; Kamiri, Kamiri; Goziyah, Goziyah (Jurnal Dinamika UMT, 2023)
The State of Psychology in the Main Figures in the novel Negri 5 Menara and novel Rantau 1 Muara by Ahmad Fuadi (Psychological Study of Literature and Its Implications for Learning Indonesian in High School). The purpose of this study was to describe the psychological state of the main character in the novel Negri 5 Menara and novel Rantau 1 Muara by Ahmad Fuadi, namely the character Alif who has an unyielding attitude and is persistent in fighting. The psychological state experienced by the main character in the novel Negri 5 Menara and the novelRantau 1 Muara includes das es (id), das ich (ego), and das ueber ich (superego). The method used is descriptive qualitative research.The results of the analysis on the novel Negri 5 Menara andnovel Rantau 1 MuaraAhmad Fuadi's work shows that the main character's personality is influenced by Id, Ego, and Super ego.